2023
DOI: 10.3389/fendo.2023.1178831
|View full text |Cite
|
Sign up to set email alerts
|

Causal effects of specific gut microbiota on bone mineral density: a two-sample Mendelian randomization study

Abstract: BackgroundRecent studies have reported that the gut microbiota is essential for preventing and delaying the progression of osteoporosis. Nonetheless, the causal relationship between the gut microbiota and the risk of osteoporosis has not been fully revealed.MethodsA two-sample Mendelian randomization (MR) analysis based on a large-scale genome-wide association study (GWAS) was conducted to investigate the causal relationship between the gut microbiota and bone mineral density (BMD). Instrumental variables for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…However, applying a stringent threshold of 5 × 10 -8 would have excluded the majority of these SNPs. Consequently, we opted for a relatively lenient yet still statistically significant threshold of 1 × 10 -05 , as supported by prior studies[ 24 , 25 ]. This threshold was set to encompass most gut microbiota-associated SNPs, ensuring that those with an R 2 < 0.001 and a physical distance (kb) of 10000 were included, thus mitigating linkage disequilibrium (LD).…”
Section: Methodsmentioning
confidence: 98%
“…However, applying a stringent threshold of 5 × 10 -8 would have excluded the majority of these SNPs. Consequently, we opted for a relatively lenient yet still statistically significant threshold of 1 × 10 -05 , as supported by prior studies[ 24 , 25 ]. This threshold was set to encompass most gut microbiota-associated SNPs, ensuring that those with an R 2 < 0.001 and a physical distance (kb) of 10000 were included, thus mitigating linkage disequilibrium (LD).…”
Section: Methodsmentioning
confidence: 98%
“…In order to fortify the reliability of the outcomes derived from MR analysis, a thorough assessment of both heterogeneity and horizontal pleiotropy was meticulously conducted ( 28 ). Cochran’s Q test estimates, derived from IVW estimates, were used to rule out heterogeneity among IVs ( 29 ). A P value < 0.05 denoted the presence of substantial heterogeneity.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, the biggest known symbiotic microbiological communities in humans are the gut microbiota, and this symbiotic relationship plays an important role in human diseases and health ( Shkoporov and Hill, 2019 ; Li et al, 2023 ). The gut microbiota affects the physiology of the host by participating in various biological processes, which include regulating immune function, regulating the oxidative stress response, maintaining anabolic balance, resisting inflammation and infection, and so on ( Adak and Khan, 2019 ; Ticinesi et al, 2019 ; Chen et al, 2023b ). An increasing number of studies have confirmed that gut microbiota dysbiosis is associated with synovitis and tenosynovitis susceptibility and progression.…”
Section: Introductionmentioning
confidence: 99%